Co–P/graphene alloy catalysts doped with Cu and Ni for efficient photocatalytic hydrogen generation. (23rd October 2017) - Zhen, Wenlong; Guo, Yueping; Wu, Yuqi; Lu, Gongxuan
Abstract : Co–Cu–P/GP exhibited excellent photocatalytic H2 evolution rates and high apparent quantum efficiencies under visible light irradiation. Abstract : Developing low-cost and high-efficiency photocatalysts for hydrogen production from solar water splitting is an intriguing and challenging objective. Co–P-based ternary alloy Co–M–P (M: Cu, Ni) cocatalysts decorated on graphene (GP) were prepared by doping Cu and Ni via an in situ synthesis strategy, and the photocatalytic performances for H2 generation were systematically studied under visible light irradiation. The structure, morphology, chemical composition, and surface electronic state of the catalysts were studied using X-ray diffraction (XRD), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS) techniques. The results indicated that the Co–Cu–P and Co–Ni–P alloys were active co-catalysts for photocatalytic H2 evolution under visible light irradiation, and the partially oxidized Co species played an important role in enhancing efficient H2 generation evidenced by XPS and XRD characterizations. For the Co–Cu–P/GP (15%) and Co–Ni–P/GP (15%) catalysts, the H2 generation rates reached 44.5 and 36.1 mmol h −1 gCo −1, respectively. The apparent quantum efficiency (AQE) of Co–Cu–P/GP (15%) and Co–Ni–P/GP (10%) samples reached 23.6 and 14.8% at 430 nm, respectively. Multi-cycle experiments indicated that both Co–Cu–P/GP (15%) and Co–Ni–P/GP (10%) catalysts presented a good stability in photocatalytic H2 evolution reactions. The Co–Ni–P and Co–Cu–P alloy materials are promising catalysts for photocatalytic H2 evolution.